Stress Levels and Coping Forms of Student Parents during Online Learning During The Covid-19 Pandemic - Fuadah, Askinatul; Sumarsih, Tri; Asti, Arnika Dwi (Prosiding University Research Colloquium, 2022)
The number of covid-19 events causing online learning (in the network). Parents of primary school students are affected by online learning that causes stress. How to solve the problem of stress in everyone is different. The aim of this research was to find out the stress levels and coping forms of student parents during online learning during the covid-19 pandemic in MI Ma'arif Ampih. The method of this research was quantitative descriptive with cross sectional approach. The sample in this study totaled 165 parents of elementary school students using total sampling. The variables in the study were stress levels and coping forms of student’s parents. The instrument used is the level of stress using watershed 42 (Depression Anxiety Stress Scale 42) which is declared valid with a reliability value of 0.8806 and a form of coping using a questionnaire that has a validity value between 0.453-0.839 with a reliability value of 0.918. Data analyzed with descriptive analysis tests or univariate tests. Respondents who numbered 165 respondents aged 21-40 years as many as 102 (61.8%), female sex as many as 117 (70.9%), high school educated as many as 62 (37.6%), housewife work as much as 86 (52.1%), and long-standing children ? 3 months as much as 139 (84.2%). The majority of mild stress levels were 66 (40.0%) and adaptive coping forms were 111 (67.3%). The conclusion is majority of stress levels in parents of students during online learning are mild stress levels and adaptive coping forms.Recommendations for researches was a reference in developing research applicatively and encourages biopsychososcultural activities in children and parents when stressed in online learning.